Areal patterns and colexifications of colour terms in the languages of Africa - (:unkn) unknown (My University, 2021)
Although colour terms are the semantic domain which has attracted the largest number of studies, notably from a typological point of view, searching the large online cross-linguistic lexical database of African languages (RefLex, Segerer & Flavier 2011-2019) pointed out several previously undetected areal colexification patterns and shared lexico-constructional patterns in a genetically balanced sample of 401 languages spoken Africa. In this paper, we illustrate several areal characteristics of colours terms along three scenarios: (i) the spread of an areal feature due to a common extra-linguistic setting (locust bean-Parkia biglobosaas the lexical source of YELLOW); (ii) two convergence phenomena, one based on a shared lexico-constructional pattern including a term for WATER, and one based on shared colexifications (RED and RIPE vs. GREEN and UNRIPE); and (iii) an areal pattern of lexical diffusion of colour ideophones, a category which was considered difficult to borrow.
Keywords: African Research